2014
DOI: 10.2131/jts.39.251
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic effects of dexmedetomidine in fetal cynomolgus monkey brains

Abstract: -The neuroprotective effects of dexmedetomidine have been reported by many investigators; however its underlying mechanism to reduce neuronal injury during a prolonged anesthesia remains unclear. In this study, we investigated the neurotoxic effects of dexmedetomidine in fetal monkey brains. In the present study, we compare the neurotoxic effects of dexmedetomidine and ketamine, a general anesthetic with a different mechanism of action, in fetal cynomolgus monkeys. Twenty pregnant monkeys at approximate gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 30 publications
(60 reference statements)
1
45
0
Order By: Relevance
“…These studies suggested that anesthesia might exhibit toxicity towards brain development. In contrast, many investigators have reported that dexmedetomidine, a potent α2-adrenoreceptor agonist with a high affinity for each of the α2-adrenoceptor subtypes (Peng et al, 2013), did not induce neurotoxicity and cellular degeneration in neither neonatal rodents nor primates (Palanisamy, 2012;Koo et al, 2014). Furthermore, remifentanil, a phenylpiperidine analgesic agent with a high affinity to μ-opioid receptors and exhibiting ultra-short-action, has gradually become established in clinical use (Rogliani et al, 2013), and large studies in vivo have validated its safety in neonates as an analgesic (Demirel et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…These studies suggested that anesthesia might exhibit toxicity towards brain development. In contrast, many investigators have reported that dexmedetomidine, a potent α2-adrenoreceptor agonist with a high affinity for each of the α2-adrenoceptor subtypes (Peng et al, 2013), did not induce neurotoxicity and cellular degeneration in neither neonatal rodents nor primates (Palanisamy, 2012;Koo et al, 2014). Furthermore, remifentanil, a phenylpiperidine analgesic agent with a high affinity to μ-opioid receptors and exhibiting ultra-short-action, has gradually become established in clinical use (Rogliani et al, 2013), and large studies in vivo have validated its safety in neonates as an analgesic (Demirel et al, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…The advantages of this model include the ability to carefully monitor hemodynamic changes in the fetus, and the ability to obtain plasma levels of dexmedetomidine, which are technically extremely difficult in neonatal rodent models. Finally, Koo et al [21] studied 20 fetal cynomolgus monkeys at 120 days of gestation. Mothers were exposed to ketamine at high dose for 12 h, or dexmedetomidine at low dose (3 μg/kg loading dose, 3 μg/kg/h for 12 h) or high dose (30 μg/kg loading dose, 30 μg/kg/h for 12 h).…”
Section: Andropoulosmentioning
confidence: 99%
“…Dexmedetomidine was mostly injected intraperitoneally, intramuscularly, or subcutaneously. In the monkey and ewe studies, it was injected intravenously and in one other study intracerebroventricularly . It was given as a single or repeated bolus with an interval varying between 1 hour and 7 days.…”
Section: Resultsmentioning
confidence: 99%